Impacts of Oceanic Mixed Layer on Hurricanes: A Simulation Experiment With Hurricane Sandy. Issue 11 (26th October 2020) - Li, Siqi; Chen, Changsheng; Wu, Zhongxiang; Beardsley, Robert C.; Li, Ming
Abstract: Influences of the ocean mixed layer (OML) dynamics on intensity, pathway, and landfall of October 2012 Hurricane Sandy were examined through an experiment using the Weather Research and Forecasting (WRF) model. The WRF model was run for two cases with or without coupling to the OML. The OML in the WRF was calculated by an oceanic mixed layer submodel. The initial conditions of the depth and mean water temperature of the OML were specified using Global‐FVCOM and Global‐HYCOM fields. The comparison results between these two cases clearly show that including the OML dynamics enhanced the contribution of vertical mixing to the air‐sea heat flux. When the hurricane moved toward the coast, the local OML rapidly deepened with an increase of storm wind. Intense vertical mixing brought cold water in the deep ocean toward the surface to produce a cold wake underneath the storm, with the lowest sea temperature at the maximum wind zone. This process led to a significant latent heat loss from the ocean within the storm and hence rapid drops of the air temperature and vapor mixing ratio above the sea surface. As a result, the storm was intensified as the central sea level pressure dropped. Improving air pressure simulation with OML tended to reduce the storm size and strengthened the storm intensity and hence provided a better simulation of hurricane pathway and landfall. Plain Language Summary: Tropical and extratropical storms are two major types of extreme weather events generating flood risk along the U.S. eastern coast. Hurricane Sandy was a storm attacking the Middle Atlantic Bight coast in 2012, with a total loss of $70 billion in the economy. Taking Hurricane Sandy, for example, we examined the influences of the oceanic mixed layer (OML) on the storm's intensity and pathway over the continental shelf. We found that when the hurricane moved toward the coast, the local OML rapidly deepened with storm wind. Intense vertical mixing brought cold water in the deep ocean toward the surface to produce a cold wake underneath the storm. This process led to a significant latent heat loss from the ocean to the air within the storm and hence rapid drops of the air temperature and vapor mixing ratio at the sea surface. As a result, the hurricane intensified as the central sea level pressure dropped. Improving air pressure simulation with OML tended to reduce the storm size and strengthened the wind intensity and hence provided a better simulation of hurricane pathway and landfall. Our finding highlighted a critical need to improve storm forecast weather model by including air‐sea interaction processes. Key Points: Strong mixing brought deep cool water upward to produce a cold wake and led a rapid change of latent heat flux into hurricane Enhanced air‐sea flux exchange in hurricane caused a drop of sea surface air temperature and hence central air pressure Including an oceanic mixed layer in WRF can significantly improve the simulation of hurricane intensity and pathway